Iskonexus designing the websites for the UP Mindanao colleges - Galope, Psalm R.
Internet users can acquire any information they need through the use and access of different websites. A good lay-out of information can maximize the usability of a website for the visitors. Also, in a single glance, a website should give the feel of the organization that it represents in the World Wide Web. The main focus of this thesis production was to create website design with high usability for the three colleges of the University of the Philippines Mindanao, namely, the College of Humanities and Social Sciences, the College of Science and Mathematics, and the School of Management. The researcher was able to achieve a design with high usability by basing the lay-out of information from the proposed UP Mindanao website and the UP System website. The researcher also chose and modified appropriate patterns and design elements from the different tribes of Mindanao to be design highlights for each college with the use of different design and principles and concepts.